Birth Cohorts in Highly Contaminated Sites: A Tool for Monitoring the Relationships Between Environmental Pollutants and Children's Health - Gaspare Drago; Silvia Ruggieri; Fabrizio Bianchi; Silvestre Sampino; Fabio Cibella (Frontiers Media S.A., 2020)
Industrial areas are characterized by the dispersion of environmental stressors that could possibly have long-term detrimental effects on both human health and the environment. Environmental contamination has been indicated to be one of the major risks for reproductive health. In this context, the effects of environmental pollution on pregnant women living in heavily polluted areas is of special interest. In fact, fetal development is a crucial phase due to the dynamic interaction between the maternal/external environments and the developing organs and tissues. Moreover, following Barker's postulate of the intrauterine origin of health and disease, the events occurring in this time window could affect future health. Birth cohorts provide the most suitable design for assessing the association between early-life and possible long-term health outcomes in highly contaminated sites. By providing an assessment of the early life environment throughout the collection of biological samples, birth cohorts offer the opportunity to study in-depth several possible confounders and outcomes by means of questionnaires and follow-ups based on clinical evaluations and bio-specimen samplings. The exposome comprises the totality of exposures from conception onwards; the birth cohort approach allows the integration of the exposures as a whole, including those related to socioeconomic status, with "omics" data from biological samples collected at birth and throughout life. In the characterization of the "fetal exposome," the placenta represents a highly informative and scarcely considered organ. For this purpose, the "Neonatal Environment and Health Outcomes" (NEHO) birth cohort has been established by enrolling pregnant women residing in contaminated sites and in surrounding areas.